Impact of a performance monitoring intervention on the timeliness of Hepatitis B birth dose vaccination in the Gambia: a controlled interrupted time series analysis - Alieu Sowe; Fredinah Namatovu; Bai Cham; Per E. Gustafsson (BMC, 2023)
Abstract Introduction The Hepatitis B virus that can cause liver cancer is highly prevalent in the Gambia, with one in ten babies at risk of infection from their mothers. Timely hepatitis B birth dose administration to protect babies is very low in The Gambia. Our study assessed whether 1) a timeliness monitoring intervention resulted in hepatitis B birth dose timeliness improvements overall, and 2) the intervention impacted differentially among health facilities with different pre-intervention performances. Methods We used a controlled interrupted time series design including 16 intervention health facilities and 13 matched controls monitored from February 2019 to December 2020. The intervention comprised a monthly hepatitis B timeliness performance indicator sent to health workers via SMS and subsequent performance plotting on a chart. Analysis was done on the total sample and stratified by pre-intervention performance trend. Results Overall, birth dose timeliness improved in the intervention compared to control health facilities. This intervention impact was, however, dependent on pre-intervention health facility performance, with large impact among poorly performing facilities, and with uncertain moderate and weak impacts among moderately and strongly performing facilities, respectively. Conclusion The implementation of a novel hepatitis B vaccination timeliness monitoring system in health facilities led to overall improvements in both immediate timeliness rate and trend, and was especially helpful in poorly performing health facilities. These findings highlight the overall effectiveness of the intervention in a low-income setting, and also its usefulness to aid facilities in greatest need of improvement.